2021
DOI: 10.1002/iid3.498
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CAIF suppresses LPS‐induced inflammation and apoptosis of cardiomyocytes through regulating miR‐16 demethylation

Abstract: Background: The long noncoding RNA, cardiac autophagy inhibitory factor (CAIF), and microRNA (miR)-16 are reported to be involved in lipopolysaccharide (LPS)-induced inflammatory responses and cell apoptosis in many diseases. Herein, we investigated the interaction between CAIF and miR-16 in sepsis-induced chronic heart failure (CHF). Methods: The expression of CAIF and miR-16 in plasma samples from sepsisinduced CHF patients (n = 60) and healthy controls (n = 60) were measured using quantitative reverse-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…A similar pattern of miR-146a expression was also observed by other researchers [61,62]. Moreover, several studies have revealed that miR-16 could inhibit LPS-induced inflammation [63]. Indeed, You et al reported findings supporting the role of miR-16 as a tumour suppressor in colorectal cancer cells (CRCs) by targeting KRAS [64].…”
Section: Lysosomal Exocytosis Ev Release and Secretory Autophagy: The...supporting
confidence: 78%
“…A similar pattern of miR-146a expression was also observed by other researchers [61,62]. Moreover, several studies have revealed that miR-16 could inhibit LPS-induced inflammation [63]. Indeed, You et al reported findings supporting the role of miR-16 as a tumour suppressor in colorectal cancer cells (CRCs) by targeting KRAS [64].…”
Section: Lysosomal Exocytosis Ev Release and Secretory Autophagy: The...supporting
confidence: 78%
“… 34 , 35 In addition, Akt and STAT6 have been reported to promote M2 polarization. 36 , 37 In the present study, exosomes overexpressing LOC441178 inactivated Akt/STAT6 signaling. Thus, it was suggested that exosomes overexpressing LOC441178 were able to inhibit macrophage M2 polarization via the inactivation of Akt/STAT6 signaling.…”
Section: Discussionsupporting
confidence: 56%
“…According to the set screening conditions, we identified 42 autophagy‐related DEGs (26 upregulated and 16 downregulated). Autophagy may play a role in regulating the occurrence and development of inflammation by activating the release of intracellular chemokines, inflammatory mediators, and cytokines through related signaling pathways, 15 such as JAK‐STAT signaling pathway, HIF‐1 signaling pathway, and toxoplasmosis. In the PPI interaction analysis of 42 differential genes, we identified a total of 42 node proteins, 75 interaction edges, and an average node degree of 3.52, indicating that these proteins have a greater level of interaction than what would be expected for a random set of proteins of the same size and degree distribution drawn from the genome.…”
Section: Discussionmentioning
confidence: 99%